2013
DOI: 10.1177/1071100713494381
|View full text |Cite
|
Sign up to set email alerts
|

Hindfoot Motion Following STAR Total Ankle Arthroplasty

Abstract: Level III, comparative case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 65 publications
3
56
1
Order By: Relevance
“…During the past 2 decades, multiple 3-dimensional multisegment foot models (3D MFMs) have been introduced and validated enabling increased application of MFM to evaluate intersegmental foot motions in various pathologic conditions. [5][6][7][8]22 Recently, an MFM with a 15 marker set (Foot3D model) was proposed, 15 and we demonstrated that this model had a comparable intrasession and intersession repeatability with other MFMs, making it suitable for evaluation of segmental foot motion during gait. 28 The objectives of this study were to evaluate the correlation between the static radiographic indices and the segmental foot motion indices measured by 3D MFM gait analysis.…”
mentioning
confidence: 83%
“…During the past 2 decades, multiple 3-dimensional multisegment foot models (3D MFMs) have been introduced and validated enabling increased application of MFM to evaluate intersegmental foot motions in various pathologic conditions. [5][6][7][8]22 Recently, an MFM with a 15 marker set (Foot3D model) was proposed, 15 and we demonstrated that this model had a comparable intrasession and intersession repeatability with other MFMs, making it suitable for evaluation of segmental foot motion during gait. 28 The objectives of this study were to evaluate the correlation between the static radiographic indices and the segmental foot motion indices measured by 3D MFM gait analysis.…”
mentioning
confidence: 83%
“…However post-operative gait parameters are still significantly diminished. The reduced motion often results in hypermobility of the midfoot causing adjacent joint OA 28, 29. Other complications following ankle arthrodesis include pain, dysfunction, non-union and malalignment 28, 29, 30.…”
Section: Clinical Relevance Of Ankle Biomechanicsmentioning
confidence: 99%
“…The reduced motion often results in hypermobility of the midfoot causing adjacent joint OA 28, 29. Other complications following ankle arthrodesis include pain, dysfunction, non-union and malalignment 28, 29, 30. Neither ankle replacement or ankle arthrodesis restores ankle normal function however total ankle replacement would appear to provide greater post-operative improvements when compared with ankle arthrodesis.…”
Section: Clinical Relevance Of Ankle Biomechanicsmentioning
confidence: 99%
“…They questioned whether subtalar arthritis existed prior to surgery as a result of the end stage ankle arthritis and subsequent gait abnormalities, or if it developed following the ankle arthroplasty. 6 The only current foot model that reports talocrural and subtalar motion during gait uses direct measurement methods with implanted bone pins. Kinematic results from this methodology compare favorably with the current fluoroscopic model, both in morphology and range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Such information would complement multiple recent studies reporting outcomes and ranges of motion. 3,6,9,11,[27][28][29]35 A better understanding of individual and composite joint contributions to hindfoot motion during ambulation could improve treatment strategies. This includes kinematic effects of ankle arthritis and subsequent treatments, both operative and non-operative.…”
Section: Introductionmentioning
confidence: 99%